SIKAP DAN KEBUTUHAN MANUSIA TERHADAP AL-QURAN - Otong Surasman (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2020)
The importance of reintroducing the holy book of the Qur'an to the public, especially among academics who are engaged in the field of the Qur'an. This paper provides important information regarding the explanation of the Qur'an about itself, so that it is hoped that with this description you can get to know the Qur'an closer and more intimately. The method used in writing this journal refers to the provisions of the thematic interpretation method, which is trying to collect verses containing the vocabulary of the Qur'an and trying to reveal the messages it contains. The goal is that Muslims can understand well the content of the verses of the Qur'an which contain information about the Qur'an itself. Allegedly while there are still many Muslims who do not know the Qur'an comprehensively in general, only among academics who are engaged in the field of the Qur'an, who may already know it, but in general there are still many who do not know. It is very important to dig out the names of the Qur'ān bi al-Qur'ān (the names of the Qur'an with the Qur'an).